(6/2x-1)-(-3/x+1)=1

Simple and best practice solution for (6/2x-1)-(-3/x+1)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6/2x-1)-(-3/x+1)=1 equation:



(6/2x-1)-(-3/x+1)=1
We move all terms to the left:
(6/2x-1)-(-3/x+1)-(1)=0
Domain of the equation: 2x-1)!=0
x∈R
Domain of the equation: x+1)!=0
x∈R
We get rid of parentheses
6/2x+3/x-1-1-1=0
We calculate fractions
6x/2x^2+6x/2x^2-1-1-1=0
We add all the numbers together, and all the variables
6x/2x^2+6x/2x^2-3=0
We multiply all the terms by the denominator
6x+6x-3*2x^2=0
We add all the numbers together, and all the variables
12x-3*2x^2=0
Wy multiply elements
-6x^2+12x=0
a = -6; b = 12; c = 0;
Δ = b2-4ac
Δ = 122-4·(-6)·0
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{144}=12$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-12}{2*-6}=\frac{-24}{-12} =+2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+12}{2*-6}=\frac{0}{-12} =0 $

See similar equations:

| X^+8x-64=0 | | 320-4x+3x+2x=360 | | 2x+(2x+2)=66 | | X3+3x2-9x-1=0 | | X3+3x^2-9x-1=0 | | X^3+3x^2-9x-1=0 | | 4y-3=6y-11 | | 320-4x-3x-2x=360 | | X³+3x²+9x=1 | | 3g=-2 | | M=-5,b=1 | | 7x=15-30^2 | | 3u+2+2-2u=1u+5 | | 2y^2=23 | | 9/25/x=3/7/15/14 | | 3(2x-5)=x-40 | | ÷5+3x4=28 | | 10y-8=5y-6 | | 16x^2-196x+369=9 | | 12/x=15/3 | | 10-3x=4(x-1) | | 7x*2-35=0 | | 45x2+10=x+20 | | ½x+2-3/2x=1,5-6 | | 5x+3(1-x)-2x=3x | | 3.3(y-9)-6=9 | | 3x+5(32-x)=114 | | t÷4-7=16 | | 14x-4-6x=6+x-2-x | | 2-3a=7-3a | | 0.027^(x-1)=11,1/9 | | y+5=y+5 |

Equations solver categories